PERBEDAAN GAYA CINTA PADA PASANGAN MAHASISWA LDR DI TINJAU BERDASARKAN JENIS KELAMIN - Naiza Ferona; Syaufi Nazmi Akmal; Fida Rafalina; Najwa Safhira; Shofiatun; Ghina Alfi Mahiroh; Nur Afni Safarina; Yulia Nanda Safitri (Jurnal Cinta Nusantara, 2025)
This study aims to examine the differences in love styles between male and female university students engaged in long-distance relationships (LDR). This topic is important because love styles influence how individuals build and maintain romantic relationships, especially when facing physical limitations such as in LDRs. The hypothesis of this study is that there are significant differences in love styles between males and females in long-distance relationships. The research employed a comparative quantitative approach with purposive sampling and used questionnaires based on Lee’s (1977) six love styles theory. Data were analyzed using the Mann-Whitney test. The results showed a significant difference in love styles between male and female students (p = 0.001). Female students tended to exhibit mania, ludus, and pragma styles, while male students were more likely to show pragma, eros, and agape styles. These findings highlight the importance of understanding gender differences in expressing love, especially to maintain relationship quality in long-distance settings